Morphological Analysis in Batak Toba Language Phrases: Death Ceremony System - Ginting, Febri Salsalina; Malau, Jason Renata Theodore; Miranti, Miranti; Silaban, Rani Enjeli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The Toba Batak community in Indonesia has a rich cultural heritage, including traditional funeral ceremonies. The language used in these ceremonies is the Toba Batak language, which is influenced by various factors such as people's names, gender, and other cultural aspects. This study aims to analyse the language structure used in the death ceremony, focusing on the phrases used in the ceremony. This research will use a qualitative approach with a qualitative descriptive method and a constructivist paradigm. Data collection techniques will include in-depth interviews and observation. The research will explore the verbal and non-verbal meanings in each of the activities in the death ceremony, the figurative language used, and the traditional bureaucratic system involved. The findings from this research will contribute to a better understanding of the language structure of Toba Batak funeral ceremonies and its cultural significance.